Automated policing: the case of body-worn video. Issue 2 (June 2019) - Bowling, Ben; Iyer, Shruti
Abstract: This paper examines the impact of body-worn video (BWV) on the police craft skills of close observation, note-taking, investigative analysis, report-writing and preparation of evidence for the courts. It explains how the technology functions and explores its surveillant, investigative, probative and regulatory applications. The evidence shows that policing tasks are being transformed by BWV cameras and analytics such as facial recognition. The paper argues that BWV exemplifies the automation of policing – the replacement of police labour with mechanical devices – and explores the implications of this for transparency, accountability, fairness and police discretion.